If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(m + 3) = 0 Reorder the terms: -8(3 + m) = 0 (3 * -8 + m * -8) = 0 (-24 + -8m) = 0 Solving -24 + -8m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -8m = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -8m = 0 + 24 -8m = 0 + 24 Combine like terms: 0 + 24 = 24 -8m = 24 Divide each side by '-8'. m = -3 Simplifying m = -3
| 13x+4=-3x+20 | | -5(7h+5)+16=-6h-9+3h | | z-47+z-42=z+21 | | 2x^6-12x^4=0 | | 259=80-x | | 10(3+10k)= | | 9x+6=6x+(-6) | | 7t-7-4=5t-8 | | 3x=3y+6w | | 5+4=20091 | | 7x+12x+15x+3+16x+7=360 | | 5(m+6)=8m | | s+s-9=s+42 | | 0.5x+2=0.375x-1 | | 8+y=7+Y | | 3n+3.6=7.5 | | k+7-8k-4= | | -3(x+4)-5x=-11+24+4-x | | 4(5x-3)=20 | | u-27+u=u+41 | | 0.5x+2=-9m+31 | | -11.875= | | 8=3y+5 | | 2xsquared-12=0 | | -3n+5-7= | | (30x)=(31x-2) | | t-37+t=t+30 | | 4h-70=12h+2 | | -7.678+(-29)= | | 8.3x-18=9x | | 14y-13y=13 | | (5x-7)+(3x+8)= |